(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Preterm labour (PTL), defined as onset of labour before 37 weeks of gestation, is a major contributor to neonatal morbidity and mortality. Magnesium plays a critical role in uterine muscle relaxation, and emerging evidence suggests that low serum magnesium levels (hypomagnesemia) may be associated with increased risk of PTL. Objective: To determine the association between hypomagnesemia and preterm labour in pregnant women admitted to a tertiary care hospital. Methods: A case-control study was conducted at the Department of Obstetrics and Gynecology, Sir Ganga Ram Hospital Lahore from 1st October 2024 to 5th April 2025. A total of 100 pregnant women (50 with preterm labour and 50 with term labour) were enrolled through consecutive sampling. Serum magnesium levels were measured at the time of admission using the xylidyl blue calorimetric method. Hypomagnesemia was defined as serum magnesium <1.8 mg/dl. Data were analyzed using SPSS version 27. Odds ratio (OR) and chi-square test were applied to assess the association. Results: The frequency of hypomagnesemia was significantly higher in the preterm group compared to the term group. The odds of preterm labour were significantly elevated among women with hypomagnesemia (OR > 1, p < 0.05). Conclusion: Hypomagnesemia is significantly associated with preterm labour. These findings suggest that serum magnesium monitoring and supplementation could be considered as part of prenatal care to potentially reduce the incidence of PTL.